2014
DOI: 10.1097/mol.0000000000000071
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in understanding the STSL locus and ABCG5/ABCG8 biology

Abstract: Progress in understanding sterolin function is beginning to show that xenosterols can be toxic and are involved on pathogenesis, and the role of ABCG5/ABCG8 may extend into other metabolic processes by altering intracellular sterol metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…The many clinical manifestations of sitosterolemia have been well-documented in a number of reviews (10,32,33). In summary, asymptomatic subjects (typically identified by cascade screening once a proband has been identified) can manifest no symptoms or signs to varying levels of affectations.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…The many clinical manifestations of sitosterolemia have been well-documented in a number of reviews (10,32,33). In summary, asymptomatic subjects (typically identified by cascade screening once a proband has been identified) can manifest no symptoms or signs to varying levels of affectations.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…For instance, sitosterolaemia sometimes resembles FH, but its management focuses on intestinal cholesterol absorption inhibition rather than statins. 27 Furthermore, patients with some dyslipidaemias do not express overt symptoms, such as atherosclerosis, until later in the disease course. When early prevention and management have been shown to delay onset of complications, there is benefit to identify and treat these individuals assertively as early as possible, as with heterozygous FH.…”
Section: Potential Benefitsmentioning
confidence: 99%
“…Some phytosterolemic patients also present with pseudo-homozygous FH, which is due to a complete failure of cholesterol efflux into bile [44,56]. Both elevated plasma cholesterol and plant sterol levels in phytosterolemia may contribute to premature vascular disease in early childhood or later in life [44], as it has been suggested that abnormal cholesterol metabolism likely contributes most strongly to the resulting atherosclerosis than plant sterol accumulation itself [32,57]. In a recent study including five phytosterolemic subjects, Hansel et al showed that, in spite of massive hypercholesterolemia and high plant sterol levels, none of the subjects had clinical symptoms of CVD or positive clinical markers of atherosclerosis [38,58].…”
Section: Cholesterol-lowering Effect Of Plant Sterols and Its Implicamentioning
confidence: 99%